2019
DOI: 10.1111/1348-0421.12736
|View full text |Cite
|
Sign up to set email alerts
|

Wild boars: A potential source of Erysipelothrix rhusiopathiae infection in Japan

Abstract: The potential role of wild boars as a source of erysipelas infection was investigated. An ELISA test of wild boar serum samples from 41 prefectures in Japan revealed that proportions of the Erysipelothrix rhusiopathiae‐positive samples were very high in all the prefectures, and the mean positive rate was 95.6% (1312/1372). Serovars of E. rhusiopathiae isolates from wild boars were similar to those of previously reported swine isolates, and all serovar isolates tested were found to be pathogenic to mice. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 18 publications
1
8
0
7
Order By: Relevance
“…1 and Table 1). In a recent nationwide survey of the seroprevalence of anti-E. rhusiopathiae antibodies in wild boars, 1,312 of 1,372 wild boars (95.6%) possessed antibodies, including all 16 wild boars (100%) captured in Nagano Prefecture [10,23]. This concurs with our results that wild boars inhabiting Nagano Prefecture are very likely to be exposed to E. rhusiopathiae.…”
Section: E Rhusiopathiaesupporting
confidence: 91%
See 1 more Smart Citation
“…1 and Table 1). In a recent nationwide survey of the seroprevalence of anti-E. rhusiopathiae antibodies in wild boars, 1,312 of 1,372 wild boars (95.6%) possessed antibodies, including all 16 wild boars (100%) captured in Nagano Prefecture [10,23]. This concurs with our results that wild boars inhabiting Nagano Prefecture are very likely to be exposed to E. rhusiopathiae.…”
Section: E Rhusiopathiaesupporting
confidence: 91%
“…This concurs with our results that wild boars inhabiting Nagano Prefecture are very likely to be exposed to E. rhusiopathiae. Shimoji et al isolated E. rhusiopathiae from the tonsils of 18 of 20 (90%) wild boars [23], also suggesting that wild boars carry E. rhusiopathiae and are a likely source of infection for domestic pigs.…”
Section: E Rhusiopathiaementioning
confidence: 99%
“…strain 2 (serotype 18) [1,2]. E. rhusiopathiae is a small, Gram-positive, slender, straight, rod-shaped bacterium that causes erysipelas in swine and many other animals [3][4][5][6][7][8]. Swine erysipelas can cause pyrexia, lameness, characteristic diamond skin lesions, and even sudden death in growing and adult swine [9].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we confirmed that a serovar 1a mutant with deletion of the whole ERH_1440 gene is as virulent as its parental strain in mice and that virulence was not altered [ 5 ]. However, it is not surprising that E. rhusiopathiae exhibits different pathogenicity between pigs and other hosts [ 10 , 15 ]; thus, it may be interesting to compare the virulence in pigs between the Ishikari strain and its mutant with a 162-bp deletion in ERH_1440.…”
mentioning
confidence: 99%